Pengaruh Orientasi, Kompetensi, dan Strategi Kewirausahaan terhadap Kinerja UMKM Kopi Muria dengan Mediasi Keunggulan Bersaing pada Klaster Kopi Muria Kudus - Munawaroh, Wahidatul; Edris, Mochamad; Faidah, Faridhatun (Jurnal Studi Manajemen Bisnis, 2024)
This research aims to analyze the influence of orientation, competence and entrepreneurial strategy on the performance of Muria coffee MSMEs by mediating competitive advantage in the Muria Kudus Coffee Cluster. This research is descriptive statistics by testing hypotheses. The sample was 150 business actors. The sampling technique used Purposive Sampling. Data collection used in this research was the questionnaire method. Instrument testing uses validity tests, reliability tests and normality tests. Analysis of the data used (SEM) Structual Equation Modeling which is operated through the AMOS program. Based on the results of hypothesis testing in this study, it shows that (1) entrepreneurial orientation has no effect on the performance of MSMEs (2) entrepreneurial competence has an effect on the performance of MSMEs, (3) entrepreneurial strategy has an effect on the performance of MSMEs, (4) orientation has an effect on competitive advantage, ( 5) entrepreneurial competence influences competitive advantage, (6) entrepreneurial strategy influences competitive advantage, (7) MSME performance influences competitive advantage. Competitive advantage is able to mediate entrepreneurial orientation on MSME performance but its influence is weak, competitive advantage is able to mediate entrepreneurial competence on MSME performance but its influence is weak and competitive advantage is able to mediate entrepreneurial strategy on MSME performance but its influence is weak